Violent dad in child shoes: a moment before ViDaCS serious game in a multi-dimensional action research promoting awareness about gender-based violence perpetrators - Arcidiacono, Caterina (Fuori Collana, 2021)
The volume describes the goals, strategies and actions of ViDaCS (Violent Dad in Child's Shoes), a project framed in the European Programme REC (Rights, Equality and Citizenship Programme 2014-2020), namely project grant number 810449.Its subtitle is A Moment Before to focus on developing an innovative multi- agency protocol for the self-assessment of intimate violence by perpetrators; it addresses the EU call purpose of preventing and combating gender-based violence under the main priority of "Treatment of perpetrators", in order to prevent reoffending.ViDaCS' book is a collective experience presenting an ecological model explaining gender-based violence, training and intervention issues on this topic; it is an experience, in the shoes of the child witnessing domestic violence, proposing alternative "domestic scenes"where the father decides and assumes "new" behaviours that avoid violent behaviour. Moreover it present and discuss a self-assessment of emotional burden and violent behaviour based on exploratory and 4.0 CTS serious game.